Editorial - Solihu, Abdul Kabir Hussain (IIUM Press, 2015)
Islam promotes a comprehensive development of human potential in all its stratifications and ramifications to enable Muslims to better perform their role as khalīfat Allāh (Allah’s vicegerent) on earth. Good governance, economic prosperity, intellectual and spiritual enrichment, social and psychological welfares, and sustainable development of human and natural resources, among others, are an integral part of the duty of khalīfat Allāh. No single Muslim state today is capable of providing all these requirements without cooperating with other states.